2020
DOI: 10.1029/2019jf005357
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Svalbard Glacier Mass Loss to Barents Sea Margins Revealed by CryoSat‐2

Abstract: The Norwegian Arctic archipelago of Svalbard is located in the most rapidly warming area of the Arctic, at the interface of Arctic and Atlantic air and ocean masses. The presence of a large number of surge‐type glaciers and the potential for rapid changes in surface mass balance and ice dynamics necessitates regularly updated mass balance assessment. This study uses swath processing of CryoSat‐2 SARIn mode data to obtain glacier elevations for 2011–2017. Individual elevation estimates are collected into 1‐km2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 83 publications
(156 reference statements)
5
40
0
Order By: Relevance
“…Glaciers in most areas of the world are losing mass as global temperatures rise in response to increased greenhouse gas concentrations in the atmosphere (e.g., Vaughan et al, 2013;Hock et al, 2019;Meredith et al, 2019;Zemp et al, 2019). In situ mass-balance observations are sparse (e.g., Zemp et al, 2020a), but with the aid of satellite and other remote-sensing data, an increasingly clear picture of glacier mass loss around the world has been appearing (e.g., Brun et al, 2017;Wouters et al, 2019;Morris et al, 2020;Shean et al, 2020). Glacier mass loss is a global phenomenon, and the rates in the early 21st century are unprecedented for the observed period (Zemp et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Glaciers in most areas of the world are losing mass as global temperatures rise in response to increased greenhouse gas concentrations in the atmosphere (e.g., Vaughan et al, 2013;Hock et al, 2019;Meredith et al, 2019;Zemp et al, 2019). In situ mass-balance observations are sparse (e.g., Zemp et al, 2020a), but with the aid of satellite and other remote-sensing data, an increasingly clear picture of glacier mass loss around the world has been appearing (e.g., Brun et al, 2017;Wouters et al, 2019;Morris et al, 2020;Shean et al, 2020). Glacier mass loss is a global phenomenon, and the rates in the early 21st century are unprecedented for the observed period (Zemp et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An accompanied significant reduction in glacier area and mass balance through the 21st century is expected [16], which makes an investigation of recent elevation and mass change patterns indispensable. Simulations have already shown negative surface mass balance and mass loss since the 1980s at variable rates [15,17,18], which is supported by several remote-sensing based negative elevation and mass change estimates over the last decades [19][20][21]. Therefore, the aim of this study is to evaluate the potential of ICESat and ICESat-2 data in Svalbard to determine elevation and mass change trends in the period of 2003-2008 to 2019.…”
Section: Introductionmentioning
confidence: 72%
“…The assessment of the used technique to derive ICESat/ICESat-2 results is provided through an in-depth analysis of the performance over Svalbard. In support of recent radar altimetry measurements [19], this use of precise laser acquisitions by ICESat/ICESat-2, with its unique properties, is expected to deliver detailed insights of elevation and mass change patterns in one of the most critical environments regarding climate change.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The Arctic has undergone large environmental changes due to increases in temperature and humidity (Box et al, 2019) and an increase in glacier mass loss has been observed in many polar regions (Morris et al, 2020). The Russian Arctic, including the archipelagos Novaya Zemlya, Severnaya Zemlya and Franz Josef Land, is one of these regions.…”
Section: Introductionmentioning
confidence: 99%